2020
DOI: 10.3892/mmr.2020.11572
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin induces apoptosis by regulating Akt and MAPK pathways in human melanoma cell A375SM

Abstract: apigenin, an aromatic compound, exhibits antioxidant, anti-inflammatory and anti-viral effects. The present study aimed to investigate the effects of apigenin on cell proliferation and apoptosis of human melanoma cells A375P and A375SM. Therefore, melanoma cells were treated with apigenin to determine its anti-proliferative and survival effects, using wound healing and MTT assays. The results revealed that melanoma cell viability was decreased in a dose-dependent manner. Furthermore, chromatin condensation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…While 100 µM is a relatively high concentration for dietary interventions and some cellular models, this concentration was selected among those found to successfully validate protein that are directly associated with apigenin in vivo [ 33 ]. Moreover, several studies have used 100 µM as part of cellular platforms [ 34 , 35 , 36 , 37 ]. Therefore, the use of 100 µM in this study is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…While 100 µM is a relatively high concentration for dietary interventions and some cellular models, this concentration was selected among those found to successfully validate protein that are directly associated with apigenin in vivo [ 33 ]. Moreover, several studies have used 100 µM as part of cellular platforms [ 34 , 35 , 36 , 37 ]. Therefore, the use of 100 µM in this study is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…Following the same thought, Woo et al investigated the effect of API (25, 50, 75, and 100 μ M) for 24 h on human melanoma cells (A375P and A375SM). Using in vitro assays, this research group has shown that the cell viability was decreased, and the expression of Bax, p53, PARP, and cleaved caspase-9 increased in a dose-dependent manner [ 48 ]. Using A2058 and A375 melanoma cell lines, Hasnat et al pointed out that API treatment (10, 20, and 50 μ M) inhibited the growth of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Deepening the experimental line, Woo et al transplanted the A375SM human melanoma cells in nude mice which were treated intraperitoneally with API (25 and 50 mg/kg). Results showed that the tumor size and weight were significantly decreased in a dose-dependent manner in the API treated groups when compared with the control group [ 48 ]. Cao et al demonstrated the antimetastatic effect of API in vivo using C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sensitivity of pre-transformed cells MCF-10A to apigenin is significantly higher, in order for it to be more effective as a chemopreventive drug rather than a therapeutic [ 391 , 392 ]. Apigenin has also been shown to modulate various anti-inflammatory pathways, in particular, in [ 393 ], apigenin weakened the growth of human melanoma cells A375SM, triggering apoptotic cell death by regulating the signaling pathways Akt and MAPK. The treatment of choriocarcinoma cells JAR and JEG3 with this flavonoid inhibited the progression and metastasis of the cells through regulation of the PI3K/Akt and ERK1/2 MAPK signaling pathways.…”
Section: Natural Compounds and Important Targets Associated With Chronic Inflammation And Oxidative Stress In Cancer Treatmentmentioning
confidence: 99%